Effects of Radial Direction and Eccentricity on Acceleration Perception. (August 2014) - Mueller, Alexandra S; Timney, Brian
Radial optic flow can elicit impressions of self-motion—vection—or of objects moving relative to the observer, but there is disagreement as to whether humans have greater sensitivity to expanding or to contracting optic flow. Although most studies agree there is an anisotropy in sensitivity to radial optic flow, it is unclear whether this asymmetry is a function of eccentricity. The issue is further complicated by the fact that few studies have examined how acceleration sensitivity is affected, even though observers and objects in the environment seldom move at a constant speed. To address these issues, we investigated the effects of direction and eccentricity on the ability to detect acceleration in radial optic flow. Our results indicate that observers are better at detecting acceleration when viewing contraction compared with expansion and that eccentricity has no effect on the ability to detect accelerating radial optic flow. Ecological interpretations are discussed.